2018
DOI: 10.1002/mp.13268
|View full text |Cite
|
Sign up to set email alerts
|

Automatic tumor segmentation in breast ultrasound images using a dilated fully convolutional network combined with an active contour model

Abstract: Purpose: Due to the low contrast, blurry boundaries, and large amount of shadows in breast ultrasound (BUS) images, automatic tumor segmentation remains a challenging task. Deep learning provides a solution to this problem, since it can effectively extract representative features from lesions and the background in BUS images. Methods: A novel automatic tumor segmentation method is proposed by combining a dilated fully convolutional network (DFCN) with a phase-based active contour (PBAC) model. The DFCN is an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 138 publications
(82 citation statements)
references
References 38 publications
1
72
1
Order By: Relevance
“…Supervised machine learning methods for radiomics include, for example, standard feature-based multi-layer perceptrons [29] , [30] , [31] and regularization networks that require the optimal minimization of functionals made of two terms: one describing the ability of the algorithm to fit the historical data and the other one describing its generalization power [21] , [22] , [23] . Ensemble methods represent a more modern approach to radiomics and, in particular, Random Forest [ 25 , 33 ] works as a large collection of decorrelated decision trees (a decision tree classifier organizes a series of test questions and conditions in a tree structure, recursively splitting training samples into subsets based on the value of a single attribute).…”
Section: Machine Learning and Deep Learning In The Radiomics Workflowmentioning
confidence: 99%
“…Supervised machine learning methods for radiomics include, for example, standard feature-based multi-layer perceptrons [29] , [30] , [31] and regularization networks that require the optimal minimization of functionals made of two terms: one describing the ability of the algorithm to fit the historical data and the other one describing its generalization power [21] , [22] , [23] . Ensemble methods represent a more modern approach to radiomics and, in particular, Random Forest [ 25 , 33 ] works as a large collection of decorrelated decision trees (a decision tree classifier organizes a series of test questions and conditions in a tree structure, recursively splitting training samples into subsets based on the value of a single attribute).…”
Section: Machine Learning and Deep Learning In The Radiomics Workflowmentioning
confidence: 99%
“…For example, Hu et al reported DSC of 0.9338 AE 0.0370 and 0.9364 AE 0.0248 for interobserver and intraobserver variability on two radiologists contouring breast tumor on ultrasound. 47 Averaged contour or consensus contour from multiple observers are thus preferred to serve as a training dataset in order to mitigate the bias and uncertainty in the segmentation results. The evaluation of the proposed method in this study showed a large SD with HD95.…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate the proposed approach, 545 test images are used. The Dice similarity coefficient (DSC), mean absolute deviation (MAD), and Hausdorff distance (HD) are applied to evaluate the results of the proposed method [15].…”
Section: B Evaluation Indexmentioning
confidence: 99%
“…The encoder part in U-net is lower as well as the decoder part in the U-net has too many feature channels to propagate trashy information to higher resolution layers by the skip connections. For instance, the noise and shadows would be magnified and propagated in the decoder part [15]. RU-net reduce the concatenation between the previous layer and higher resolution layer, which could avoid the shadow information propagating to the higher resolution layers.…”
Section: Introductionmentioning
confidence: 99%